Outcome of Mechanical Thrombectomy for Acute Ischemic Strokein Tertiary Hospital - พิทักษ์ทอง, วชิรชัย; สมบูรณ์ทรัพย์, ธนบัตร; พันธุ์คงทรัพย์, อานุภาพ; อวัยวานนท์, อภินันท์ (Thai Journal of Neurological Surgery, 2025)
Background: Mechanical thrombectomy has been studied and developed into one of the standard treatment modalities for patients with acute ischemic stroke. In the context of a tertiary care hospital, Bhumibol Adulyadej Hospital, Royal Thai Air Force, has implemented this treatment since 2016. This study aimed to collect and analyze treatment outcomes and factors associated with prognosis. Methods: A retrospective descriptive study was conducted on 62 patients treated between January 1, 2016, and August 31, 2023. Treatment outcomes were evaluated using the modified Rankin Scale (mRS) at 90 days, and factors influencing clinical outcomes were analyzed. Results: Thirty-two patients (51.6%) achieved good outcomes (mRS 0–2), and 13 patients (21.0%) died. Successful recanalization, defined as a modified Thrombolysis in Cerebral Infarction score (mTICI) of 2b–3, was significantly associated with favorable outcomes (odds ratio [OR] 0.158, 95% confidence interval [CI] 0.035–0.715, P = 0.017). Conclusion: Patients with acute ischemic stroke undergoing mechanical thrombectomy at our institution achieved good outcomes (mRS 0–2) at rates comparable to international standards. Successful recanalization was a significant predictor of favorable clinical outcomes.